2005
DOI: 10.1191/0267658305sr257oa
|View full text |Cite
|
Sign up to set email alerts
|

Eye-movement recording as a tool for studying syntactic processing in a second language: a review of methodologies and experimental findings

Abstract: The complex trace of saccades, fixations and regressions that the eyes make while taking in a line of text is unquestionably one of the richest accounts available as concerns the process of reading. Recording these jumps, stops and re-takes provides a to-the-letter, millisecond-precise report of the readers’ immediate syntactic processing as well as revisions thereof. In addition, the influence of innumerable factors -from low-level visual conditions to high-level pragmatic cues - on the reading process can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 42 publications
2
78
0
Order By: Relevance
“…However, it must be noted that the absolute amount of evidence for this is still small, and more psycholinguistic research on this issue needs to be done. Using a methodology like eye-tracking, and in particular first pass reading times, would provide evidence about the fast and automatic processing of formulaic sequences from a different perspective (Frenck-Mestre 2005). If the current pattern of results were replicated using the eye-tracking methodology, this would provide even stronger evidence for the processing advantage of formulaic sequences.…”
Section: Resultsmentioning
confidence: 76%
“…However, it must be noted that the absolute amount of evidence for this is still small, and more psycholinguistic research on this issue needs to be done. Using a methodology like eye-tracking, and in particular first pass reading times, would provide evidence about the fast and automatic processing of formulaic sequences from a different perspective (Frenck-Mestre 2005). If the current pattern of results were replicated using the eye-tracking methodology, this would provide even stronger evidence for the processing advantage of formulaic sequences.…”
Section: Resultsmentioning
confidence: 76%
“…The P600 is evoked by a number of different syntactic manipulations such as violations of agreement (Hagoort, Brown, & Groothusen, 1993;Osterhout & Mobley, 1995;Vos, Gunter, Kolk, & Mulder, 2001), of verb inflection (Friederici, Pfeifer, & Hahne, 1993;Gunter, Stowe, & Mulder, 1997), of case inflection (Münte, Heinze, Matzke, Wieringa, & Johannes, 1998), of pronoun inflection (Coulson, King, & Kutas, 1998), of phrase structure (Friederici et al, 1993;Hahne & Friederici, 1999;Neville, Nicol, Barss, Forster, & Garrett, 1991), of case marking (Coulson et al, 1998;Friederici & Frisch, 2000;Frisch & Schlesewsky, 2001, 2005, and of verb-argument structure (Friederici & Frisch, 2000;Frisch, Hahne, & Friederici, 2004;Osterhout, Holcomb, & Swinney, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…However, eye-movement recordings show that highly proficient L2 readers can be "garden-pathed" (i.e., go by the preferred reading of a sentence structure (Frazier & Rayner, 1982) in the same manner as L1 readers (i.e., FrenckMestre & Pynte, 1997;Juffs & Harrington, 1996)). However, sensitivity to syntactic ambiguity appears to be critically influenced by AoA, proficiency, and cross-linguistic syntactic similarity (for a review see Frenck-Mestre, 2005). As reported in Dussias (2003), Fernàndez (1999) presented results that late learners of English (L1 Spanish) used L1 parsing strategies while processing syntactic ambiguity (relative clause attachment (RC)) in English), while early learners varied in their attachment preference with some showing a monolingual profile and others showing late learner profiles.…”
Section: Introductionmentioning
confidence: 99%
“…And -just to be sure it is mentioned here-research using on-line measures such as eyetracking and self-paced reading has repeatedly demonstrated that even though native speakers and non-native speakers might arrive at the same comprehension of sentences, non-native readers are consistently slower than natives in reading sentences no matter how advanced the former are (e.g., Frenck-Mestre, 2005).…”
Section: Ii3 Is Skill Development Amenable To Instruction?mentioning
confidence: 93%